A Review of Criminal Law and Islamic Law on the Role And Ethics of Debt Collectors in the Perspective of Hadith Interpretation - Nurhikmah, Aulia (Yayasan Mentari Madani, 2024)
Enough money can buy everything we need and want, which is why everyone strives to earn money. Problems arise when the money is not available when the need is met. This can be addressed with a payment system called credit, which allows us to purchase items without having to pay immediately. With credit, we can pay for items according to our ability and within a certain timeframe, making it easier for us to obtain what we want without having to have a lot of cash on hand. However, credit allows borrowers to pay off their debts with interest over a certain period. As a result, the presence of debt collectors has expanded beyond the banking sector. Although other businesses with billing, such as leasing, provide credit to customers who want to buy cars or other vehicles on credit. However, in practice, debt collectors rarely commit legal violations such as intimidation, threats, and physical or psychological violence. Forced collection is considered a legal violation because debt collectors are categorized as general criminal offenses in the Criminal Code (KUHP), which consists of: a. Crimes and b. Offenses. The purpose of this research is to study how Islamic law regulates the role and ethics in the debt collection process, particularly how the profession of debt collectors is often associated with intimidation and violence, raising questions about its alignment with Islamic values. This study emphasizes elements of justice, compassion, and prevention of oppression as the main pillars of the debt collection process through the interpretation of hadith. Additionally, this article offers alternative debt collection solutions that are Sharia-compliant and ethical. The results of this study indicate that from an Islamic perspective, the role of debt collectors must be accompanied by ethics that reflect justice and humanitarian principles contained in the hadith